Outcomes of transcatheter aortic valve replacement in patients with and without atrial fibrillation: Insight from national inpatient sample. (3rd October 2021) - Khan, Muhammad Zia; Zahid, Salman; Khan, Muhammad U.; Kichloo, Asim; Jamal, Shakeel; Minhas, Abdul Mannan Khan; Ullah, Waqas; Sattar, Yasar; Mir, Tanveer; Balla, Sudarshan; Munir, Muhammad Bilal
ABSTRACT: Background: Atrial fibrillation (AF) is one of the most frequent rhythm disturbance encountered in the population in general. Our study aims to evaluate the in-hospital outcomes of TAVR with AF. Methods: We used National Inpatient Sample database from 2011 to 2018. Baseline characteristics and in-hospital outcomes were evaluated in TAVR based on AF status or not in both unmatched and propensity-matched cohorts. Results: A total of 215, 938 patients underwent TAVR during our study period and out of these AF was encountered in 89, 587 (41.5%) patients. AF patients undergoing TAVR had a higher mean age and had an increased burden of key co-morbidities in the unmatched cohort. With propensity matched 1:1 analysis, AF had higher mortality as compared to no-AF group (2.4% vs. 2.1%, p < 0.01). The rate of cardiogenic shock (2.9% vs 2.1%), respiratory complications (9.9% vs 8.2%), acute kidney injury (15.6% vs 12.0%), vascular complications (5.0% vs 4.7%), and blood transfusion (10.4% vs 8.6%) was higher in TAVR patients with AF. A lower proportion of patients had routine discharge to home for TAVR with AF (80.8% vs 74.4%). Cost of hospitalization (23, 0171[SD, 20, 5242] vs 210, 608[28, 4203]) and length of stay (5.7[SD, 11.8] vs 4.29[7.2] days) were considerably higher in patients undergoing TAVR with AF. Conclusion: Patients undergoing TAVR with concomitant AF tended to have increased mortality, complications, length, and cost of stay compared to non-AF patients.